Tuberculosis the great mimicker: Five unusual cases - Shohael Mahmud Arafat; Chowdhury Adnan Sami; Sudip Kumar Banik; Refaya Tasnim; Nazmun Naher; Md Altaf Hossain; Md Mizanur Rahman Khan; Abed Hussain Khan (Clinical Infection in Practice, 2024)
Background: There are wide varieties of clinical manifestations of Tuberculosis (TB). Extrapulmonary tuberculosis (EPTB) patients usually come with an atypical presentation, are difficult to suspect, and frequently involve sites that are very hard to access, and invasive procedures are usually required for diagnosis. We are presenting five cases of atypical presentations of TB here. Case reports: The first case presented acute flaccid paraparesis with right loin pain, ultimately diagnosed as tubercular psoas abscess inducing acute inflammatory demyelinating polyneuropathy. The second case presented with hematemesis, dysphagia, weight loss, and a rare case of esophageal TB was diagnosed. The third case presented with painful multiple bony lytic lesions and was diagnosed as a case of multifocal skeletal TB. The fourth case presented multiple abscesses at different skin sites, leading to a diagnosis of metastatic tubercular abscesses. The fifth case was an elderly female who presented with right hip joint pain, eventually diagnosed as tubercular hip arthritis. Conclusion: EPTB is a great mimicker and has been a challenging medical condition due to the divergence of presentations. High clinical suspicion and vigilance can lead to an early diagnosis and survival of patients.